Reading difference: picture book retellings as contexts for exploring personal meanings of race and culture. (26th February 2015) - Lysaker, Judith; Sedberry, Tiffany
Abstract: In racially and culturally homogeneous school settings, opportunities for children to interact with those who are unlike themselves are not always available. Picture book retellings provide contexts within which students are exposed to racial and cultural differences by allowing them to engage in vicarious events with people they might not otherwise encounter. In this article, the authors explore two fourth graders' aided and unaided picture book retellings. They argue that retellings are dialogic literacy events that provide children with opportunities to explore difference through social imagination and develop empathetic response to a wide range of fictional others.